Viral load as a risk factor of reverse transcriptase inhibitor drug resistance mutation in antiretroviral-treated people living with HIV/AIDS - Hutapea, Hotma Martogi Lorensi; Kridaningsih, Tri Nury; Prasetyo, Khoirul Huda; Antwi, Milton Boaheng (Faculty of Medicine, Universitas Trisakti, 2021)
Background The human immunodeficiency virus type 1 (HIV-1) is a major contagion faced by the population of Indonesia. The success of antiretroviral treatment (ART) is threatened by the emergence of drug resistance mutations (DRM). The aim of this study was to determine the association between CD4 count, CD4 count changes, viral load, adherence to therapy, and therapy history in the presence of DRM in people living with HIV/AIDS (PLWHA). MethodsThis was a cross-sectional study involving 269 adults who underwent antiretroviral (ARV) therapy for at least 6 months. The frequencies of DRM and polymorphisms were measured by partial amplification of the reverse transcriptase (RT) gene using RT-nested PCR on samples with viral loads of >1000 copies/mL. Sequencing was performed using the Sanger method, and edited by BioEdit. The edited sequences were submitted to http://hivdb.stanford.edu for DRM determination. Respondents’ medical data, CD4 count, viral load, and DRM were analyzed by simple and multiple logistic regression. ResultsThe multiple logistic regression analysis showed a significant association of CD4 count (aOR=12.47; 95% CI: 1.45 -107.39; p=0.023) and viral load at the time of study (aOR=29.56; 95% CI: 3.47-251.52; p=0.002) with the presence of DRM in respondents. ARV substitution history was not associated with the presence of DRM. There were 17 respondents (6.3%) carrying HIV-1 DRM, with M184V/I (11 sequences) as the most frequent pattern of NRTI resistance, and K103 (9 sequences) as that of NNRTI resistance. ConclusionThis study demonstrated that viral load at the time of the study was the most influential determinant factor for the presence of DRM in PLWHA.